Design a high gain UWB mimo uniplanar monopole antenna with FSS array for metallic object microwave imaging - Abdulhasan, Raed Abdulkareem (2019)
Ultra-wideband (UMB) system plays an important role in microwave imaging (MWI) applications due to its broad bandwidth, non-ionizing radiation, and cost-efficiency. this study involves the design and development phases for the optimum solution of UMB antenna's issues. In the design phase, a compact uniplanar hexagon UMB monopole antenna with a coplanar waveguide (CPW) feed is designed. The proposed UMB antenna has an oscillate impedance (za) of 50Ω. A meander-line notch filter is loaded on the designed antenna that achieves a high rejection (S11=-1.75 dB) at the band of 3.0 GHz for 5G mid-band. A T-strip is inserted between the two proposed MIMO antennas to improve the isolation. Moreover, the smallest uniplanar UWB frequency selective surface (FSS) unit cell size (0.095λx0.095λ) is miniaturized on the FR4 substrate. The simulations are compared with the equivalent circuit models of the proposed solutions, then validate with the measurement results. In the development phase, the hexagonal monopole MIMO antenna, The CPW feed, the isolation T-strip, and the 3 x 7 FSS (IMAF) achieves a bandwidth of 3-11.7 GHz, unidirectional radiation patterns, mutual coupling (S21 about -27 dB) and gain (6-8.5 dBi), and it better than the existing antennas of 3.1-10.6 GHz, _20 dB, and 5.5 dBi, respectively. Additionally, the baggage-scanner scheme is developed as a case study to evaluate the IMAF is 55% higher than that of the MIMO antenna without an FSS array. Thus, the proposed IMAF detects the smallest (0.5 x 2 cm2 ) metallic object with a location accuracy of ¥ o.5 cm compared with the recent simulation study of (0.6 x 0.h cm2 and ±1.1 cm, respectively). A good agreement is observed between the simulated and measured images of the MWI. Consequently, the IMAF is proved to be applicable as part of the detection system for low-cost and non-intricate baggage-scanner imaging to detect metallic objects.